2019
DOI: 10.1016/j.pestbp.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in the voltage-gated sodium channel gene associated with pyrethroid resistance in Iranian populations of the European red mite Panonychus ulmi

Abstract: Point mutations in the voltage-gated sodium channel gene associated with pyrethroid resistance in Iranian populations of the European red mite Panonychus ulmi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…For the Tetranychus species, several mutations in the VGSC have also been associated with decreased sensitivity towards Type I and Type II pyrethroids: point mutations M918L/T or L925M in the intracellular linker connecting transmembrane segments IIS4 and IIS5 (where M918L was found in combination with F1534S in IIIS6), L1024V at the terminus of the IIS6 transmembrane segment of the sodium channel and F1538I in domain IIIS6 ( M. domestica numbering) [ 16 , 17 , 18 , 19 , 20 , 21 ] ( Figure 1 ) ( Table S1 ). Similar VGSC mutations have also been reported for other spider mites such as Panonychus citri and Panonychus ulmi , but also in other mites and ticks, including the cattle tick Rhipicephalus microplus , the Varroa mite, the poultry red mite Dermanyssus gallinae and predatory mites such as Phytoseiulus persimilis [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…For the Tetranychus species, several mutations in the VGSC have also been associated with decreased sensitivity towards Type I and Type II pyrethroids: point mutations M918L/T or L925M in the intracellular linker connecting transmembrane segments IIS4 and IIS5 (where M918L was found in combination with F1534S in IIIS6), L1024V at the terminus of the IIS6 transmembrane segment of the sodium channel and F1538I in domain IIIS6 ( M. domestica numbering) [ 16 , 17 , 18 , 19 , 20 , 21 ] ( Figure 1 ) ( Table S1 ). Similar VGSC mutations have also been reported for other spider mites such as Panonychus citri and Panonychus ulmi , but also in other mites and ticks, including the cattle tick Rhipicephalus microplus , the Varroa mite, the poultry red mite Dermanyssus gallinae and predatory mites such as Phytoseiulus persimilis [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionsupporting
confidence: 69%
“…To examine whether the difference in susceptibility to bifenthrin could be explained by target-site resistance mutations, we screened for known mutations in the VGSC and found that three out of four bifenthrin-resistant strains carried the L1024V mutation in the VGSC (MR-VL, MR-VLi and ES1). Next to the L1024V mutation, the most resistant strain in this study, ES1, also showed the presence of the F1538I mutation, which has been frequently associated with pyrethroid resistance [ 16 , 17 , 18 , 19 , 30 , 91 , 92 , 93 , 94 ]. We did find the F1538I mutation in the VGSC of the susceptible strain UK4, but it was at a low frequency and therefore probably did not result in resistance in our bioassays.…”
Section: Discussionmentioning
confidence: 93%
“…Tabela 2. Studije koje potvrđuju pojavu rezistentnosti kod P. ulmi na određene aktivne materije koje su danas u upotrebi prema Badieinia et al (2020) Aktivna materija Literaturni izvor abamektin* Nauen et al, 2001;Çağatay et al, 2014;Rameshgar et al, 2019bdikofol Pree et al, 2005fenazakvin Auger et al, 2003fenpiroksimat Nauen et al, 2001Yaghoobi et al, 2021heksitiazoks* Thwaite, 1991Nauen et al, 2001;Pree et al, 2005klofentezin* Thwaite, 1991Nauen et al, 2001;Pree et al, 2005;Kramer andNauen, 2011 piretroidi Nauen et al, 2001;Rameshgar et al, 2019apiridaben* Nauen et al, 2001Kramer andNauen, 2011 spirodiklofen* Kramer andNauen, 2011;Bajda et al, 2015tebufenpirad* Auger et al, 2003 aktivne materije koje su registrovane u Srbiji za suzbijanje P. ulmi na jabuci prema (Grupa autora, 2020) Primera radi, spirodiklofen i spiromesifen su dva ciklična keto-enolna jedinjenja koja pokazuju veoma dobro akaricidno delovanje na fi tofagne grinje i nekoliko štetnih vrsta insekata (Dekeyser, 2005). Prema Bretschneider et al (2012) i Bajda et al (2015, ova jedinjenja inhibiraju acetil-CoA karboksilazu (ACCase) i ometaju biosintezu lipida kod grinja i insekata.…”
Section: Mehanizmi Rezistentnosti I Načini Delovanja Akaricida Kod P Ulmiunclassified
“…7 Many mutations which are in different position of insect sodium channel genes were reported in insect field populations. [8][9][10][11] Some mutations have been proved to reduce the combination between insect sodium channels with pyrethroid in Xenopus oocytes. 12,13 Some mutations are identified in multiple insect species, but some mutations are found only in single species.…”
Section: Introductionmentioning
confidence: 99%
“…A major molecular mechanism of insect resistance to pyrethroids is known as knockdown (kdr) 7 . Many mutations which are in different position of insect sodium channel genes were reported in insect field populations 8–11 . Some mutations have been proved to reduce the combination between insect sodium channels with pyrethroid in Xenopus oocytes 12,13 .…”
Section: Introductionmentioning
confidence: 99%